Protocol for generating customizable and reproducible plots of sequencing coverage data using the seqNdisplayR package - Søren Lykke-Andersen; Jérôme O. Rouvière; Manfred Schmid; Maria Gockert; Torben Heick Jensen (STAR Protocols, 2024)
Summary: The widespread usage of next-generation sequencing methods for functional genomics studies requires standardized tools for consistent visualization of the associated data. Here, we present seqNdisplayR, an R package for plotting standard sequencing data coverage within a genomic region of interest in a customizable and reproducible manner. We describe steps for installing software, preparing data files, choosing options, and plotting data. This tool is readily available for users with no prior experience with R through the “Shiny app” interface.For complete details on the use and execution of this protocol, please refer to Lykke-Andersen et al.,1 Gockert et al.,2 and Rouviere et al.3 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.